Staatlichkeit in der Schweiz Regieren und verwalten vor der neoliberalen Wende - Criblez, Lucien; Ruoss, Thomas; Rothen, Christina (Chronos Verlag, 2016)
Governance and Public Administration in Switzerland Transformations before the Neoliberal Turn How did the state, its administration and its tasks change within the second half of the 20th century? To answer this question the articles in this book ana-lyze administrative practices as a crucial manifestation of statehood from the 1960s to the 1990s. Although the multilevel political system served as a stabi-lizing factor, a social and cultural readiness to reform also took shape, which has had a lasting impact on the management process. A neoliberal turn did not result immediately but a discussion in that direction was opened up. The book deals with the structure-building effect of subsidies, the commercializa-tion and privatization of state tasks, as well as with effects of scientific exper-tise on administration and politics. Transformations in education, youth, eco-nomic, migration and health policy are highlighted. Three different disciplinari-an viewpoints - history, history of education and political science are synthe-sized in the conclusion, which also outlines a relevant research program for contemporary history.